2014
DOI: 10.1155/2014/210717
|View full text |Cite
|
Sign up to set email alerts
|

Condition Monitoring of Blade in Turbomachinery: A Review

Abstract: Blade faults and blade failures are ranked among the most frequent causes of failures in turbomachinery. This paper provides a review on the condition monitoring techniques and the most suitable signal analysis methods to detect and diagnose the health condition of blades in turbomachinery. In this paper, blade faults are categorised into five types in accordance with their nature and characteristics, namely, blade rubbing, blade fatigue failure, blade deformations (twisting, creeping, corrosion, and erosion),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…The system presented in the paper is intended to use for monitoring the stress of blade in an industrial steam turbine. The methods of structural health monitoring cover contactless tip-timing techniques using blade-tip vibrometers based on capacitive [13], magneto-resistive [14] or optical sensors [15], as well as contact techniques using fibre grating sensors [16] or mostly used strain gauges [17]. The latter method enables to monitor blade fatigue failures by studying the characteristic of flow-induced resonant vibration.…”
Section: Applications For Wireless and High-temperature Monitoringmentioning
confidence: 99%
“…The system presented in the paper is intended to use for monitoring the stress of blade in an industrial steam turbine. The methods of structural health monitoring cover contactless tip-timing techniques using blade-tip vibrometers based on capacitive [13], magneto-resistive [14] or optical sensors [15], as well as contact techniques using fibre grating sensors [16] or mostly used strain gauges [17]. The latter method enables to monitor blade fatigue failures by studying the characteristic of flow-induced resonant vibration.…”
Section: Applications For Wireless and High-temperature Monitoringmentioning
confidence: 99%
“…The intension was to detect the faults at the early stage before the catastrophic failure take place. An extensive review on this subject can be found in ref [1][2][3]. Blade deformation such as blade twisting, creep, erosion, and corrosion are common faults that occurred in turbomachinery.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods of rotor blades diagnosis have been developed and tested, such as eddy current [1], ultrasonic [2,3], thermographic [4,5], radiographic [4,6], and vibration methods [7][8][9][10]. A comprehensive literature review of various blade faults detection methods has been presented by Abdelrhman et al [11].…”
Section: Introductionmentioning
confidence: 99%